Psychotropic Drugs and Reproductive Health in Women and Men: A Review of Current Evidence - Pierzyńska, Klaudia; Godyń-Müller, Kacper; Brzeziński, Michał; Zeigner, Martin; Błaszczyk, Joanna; Grześkowiak, Michał; Kasprzak, Mateusz; Pelant, Hanna; Kulak, Bartosz; Majchrzak, Zuzanna (Journal of Education, Health and Sport, 2026)
Fertility disorders are becoming an increasingly significant public health concern, especially in developed countries. Alongside lifestyle and environmental influences, psychiatric disorders and their pharmacological treatment may also adversely affect reproductive health. Psychotropic drugs — including antidepressants, antipsychotics, benzodiazepines, mood stabilizers, and methylphenidate — have been linked to hormonal imbalances, sexual dysfunction, impaired spermatogenesis, and reduced fertility in both females and males. Current evidence suggests that these medications may influence reproductive function through several mechanisms, such as endocrine disturbances, hyperprolactinemia, oxidative stress, and dysregulation of the hypothalamic–pituitary–gonadal axis. Selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants are most commonly associated with reduced semen quality and sexual dysfunction, while antipsychotics are strongly linked to prolactin-related reproductive disturbances. Benzodiazepines have been connected with decreased libido and erectile dysfunction. Among mood stabilizers, valproic acid and carbamazepine appear to exert the most unfavorable effects on fertility in both sexes, whereas evidence concerning methylphenidate remains limited and inconsistent. Research also indicates that adverse reproductive effects may differ between women and men. Nevertheless, the overall relationship between psychotropic medications and fertility is still not fully understood, as many available studies are outdated, methodologically limited, or present conflicting findings. Moreover, it remains difficult to separate the effects of the medications themselves from the impact of psychiatric illnesses, chronic stress, anxiety, and depression. Therefore, further well-designed contemporary studies are needed to clarify the influence of psychotropic drugs on reproductive health in both women and men.